The Effect of Tax Avoidance and Product Market Competition on Cost Stickiness with Business Strategy as A Moderation - Putri, Febby Wulandari; Diyanti, Ferry (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
Managers' decisions regarding company resources can impact company costs significantly when sales activity decreases, resulting in cost stickiness. These costs can be covered by cash savings from tax avoidance or by pruning unused resources when the company's product market competition increases. Implementation of strategy also has an impact on company cost management. This research aims to provide empirical evidence that tax avoidance and product market competition influence cost stickiness, which is moderated by business strategy. This type of research is quantitative, using secondary data. Using purposive sampling, 33 manufacturing sector companies listed on the IDX for 2013-2022 were obtained. Data analysis used SPSS 26 software. The research results obtained were: (1) Tax avoidance has a positive and significant effect on cost stickiness; (2) Product market competition has a negative and significant effect on cost stickiness; (3) The prospector's business strategy cannot strengthen the influence of tax avoidance on cost stickiness; (4) Business strategy defenders cannot strengthen the influence of product market competition on cost stickiness